Never race a runaway pumpkin - Applegate, Katherine (Applegate, Katherine. Roscoe Riley rules, 2009)
Roscoe is determined to guess the weight of a giant pumpkin in order to win books for his school library and candy for himself, but is overwhelmed by superstitions, especially about a certain black kitten.